Step
*
2
of Lemma
rv-compass-compass-lemma
1. a : ℝ^2
2. b : ℝ^2
3. c : ℝ^2
4. d : ℝ^2
5. a ≠ c
6. ↓∃p,q:ℝ^2. (((d(a;b) = d(a;p)) ∧ (d(c;d) = d(c;q))) ∧ (d(c;p) ≤ d(c;d)) ∧ (d(a;q) ≤ d(a;b)))
7. ∃u,v:ℝ^2
    (((||u|| = d(a;b)) ∧ (||u - c - a|| = d(c;d)))
    ∧ ((||v|| = d(a;b)) ∧ (||v - c - a|| = d(c;d)))
    ∧ (((d(a;b)^2 - d(c;d)^2) + ||c - a||^2^2 < (r(4) * ||c - a||^2 * d(a;b)^2))
      
⇒ (r2-left(u;c - a;λi.r0) ∧ r2-left(v;λi.r0;c - a))))
⊢ ∃u,v:{p:ℝ^2| ab=ap ∧ cd=cp} 
   ((↓∃p,q:ℝ^2. (((d(a;b) = d(a;p)) ∧ (d(c;d) = d(c;q))) ∧ (d(c;p) < d(c;d)) ∧ (d(a;q) < d(a;b))))
   
⇒ (r2-left(u;c;a) ∧ r2-left(v;a;c)))
BY
{ Assert ⌜∀x,y,z:ℝ^2.  (d(x;y) = d(x;z) 
⇐⇒ ||z - x|| = d(x;y))⌝⋅ }
1
.....assertion..... 
1. a : ℝ^2
2. b : ℝ^2
3. c : ℝ^2
4. d : ℝ^2
5. a ≠ c
6. ↓∃p,q:ℝ^2. (((d(a;b) = d(a;p)) ∧ (d(c;d) = d(c;q))) ∧ (d(c;p) ≤ d(c;d)) ∧ (d(a;q) ≤ d(a;b)))
7. ∃u,v:ℝ^2
    (((||u|| = d(a;b)) ∧ (||u - c - a|| = d(c;d)))
    ∧ ((||v|| = d(a;b)) ∧ (||v - c - a|| = d(c;d)))
    ∧ (((d(a;b)^2 - d(c;d)^2) + ||c - a||^2^2 < (r(4) * ||c - a||^2 * d(a;b)^2))
      
⇒ (r2-left(u;c - a;λi.r0) ∧ r2-left(v;λi.r0;c - a))))
⊢ ∀x,y,z:ℝ^2.  (d(x;y) = d(x;z) 
⇐⇒ ||z - x|| = d(x;y))
2
1. a : ℝ^2
2. b : ℝ^2
3. c : ℝ^2
4. d : ℝ^2
5. a ≠ c
6. ↓∃p,q:ℝ^2. (((d(a;b) = d(a;p)) ∧ (d(c;d) = d(c;q))) ∧ (d(c;p) ≤ d(c;d)) ∧ (d(a;q) ≤ d(a;b)))
7. ∃u,v:ℝ^2
    (((||u|| = d(a;b)) ∧ (||u - c - a|| = d(c;d)))
    ∧ ((||v|| = d(a;b)) ∧ (||v - c - a|| = d(c;d)))
    ∧ (((d(a;b)^2 - d(c;d)^2) + ||c - a||^2^2 < (r(4) * ||c - a||^2 * d(a;b)^2))
      
⇒ (r2-left(u;c - a;λi.r0) ∧ r2-left(v;λi.r0;c - a))))
8. ∀x,y,z:ℝ^2.  (d(x;y) = d(x;z) 
⇐⇒ ||z - x|| = d(x;y))
⊢ ∃u,v:{p:ℝ^2| ab=ap ∧ cd=cp} 
   ((↓∃p,q:ℝ^2. (((d(a;b) = d(a;p)) ∧ (d(c;d) = d(c;q))) ∧ (d(c;p) < d(c;d)) ∧ (d(a;q) < d(a;b))))
   
⇒ (r2-left(u;c;a) ∧ r2-left(v;a;c)))
Latex:
Latex:
1.  a  :  \mBbbR{}\^{}2
2.  b  :  \mBbbR{}\^{}2
3.  c  :  \mBbbR{}\^{}2
4.  d  :  \mBbbR{}\^{}2
5.  a  \mneq{}  c
6.  \mdownarrow{}\mexists{}p,q:\mBbbR{}\^{}2.  (((d(a;b)  =  d(a;p))  \mwedge{}  (d(c;d)  =  d(c;q)))  \mwedge{}  (d(c;p)  \mleq{}  d(c;d))  \mwedge{}  (d(a;q)  \mleq{}  d(a;b)))
7.  \mexists{}u,v:\mBbbR{}\^{}2
        (((||u||  =  d(a;b))  \mwedge{}  (||u  -  c  -  a||  =  d(c;d)))
        \mwedge{}  ((||v||  =  d(a;b))  \mwedge{}  (||v  -  c  -  a||  =  d(c;d)))
        \mwedge{}  (((d(a;b)\^{}2  -  d(c;d)\^{}2)  +  ||c  -  a||\^{}2\^{}2  <  (r(4)  *  ||c  -  a||\^{}2  *  d(a;b)\^{}2))
            {}\mRightarrow{}  (r2-left(u;c  -  a;\mlambda{}i.r0)  \mwedge{}  r2-left(v;\mlambda{}i.r0;c  -  a))))
\mvdash{}  \mexists{}u,v:\{p:\mBbbR{}\^{}2|  ab=ap  \mwedge{}  cd=cp\} 
      ((\mdownarrow{}\mexists{}p,q:\mBbbR{}\^{}2.  (((d(a;b)  =  d(a;p))  \mwedge{}  (d(c;d)  =  d(c;q)))  \mwedge{}  (d(c;p)  <  d(c;d))  \mwedge{}  (d(a;q)  <  d(a;b))))
      {}\mRightarrow{}  (r2-left(u;c;a)  \mwedge{}  r2-left(v;a;c)))
By
Latex:
Assert  \mkleeneopen{}\mforall{}x,y,z:\mBbbR{}\^{}2.    (d(x;y)  =  d(x;z)  \mLeftarrow{}{}\mRightarrow{}  ||z  -  x||  =  d(x;y))\mkleeneclose{}\mcdot{}
Home
Index